National Repository Infrastructure and Open Access Challenges: The Croatian Perspective - Ivana Matijević; Ivona Milovanović (Liber Quarterly: The Journal of European Research Libraries)
Repositories are one of the key infrastructure components in achieving the goals of open science. In response to legal obligations, emerging trends, and challenges in open science, several Croatian institutions jointly established a national digital repository infrastructure in 2015 - the DABAR system (Digital Academic Archives and Repositories). Its purpose is to provide a unified space for storing, preserving, and ensuring open access to the scholarly output of scientists and institutions within the Croatian science and higher education system.